Beta Lactams Plus Daptomycin Combination Therapy for Infective Endocarditis: An Italian National Survey (BADAS) - Silvia Corcione; Tommaso Lupia; Carlo Pallotto; Daniele Roberto Giacobbe; Ilaria De Benedetto; Giacomo Stroffolini; Simone Mornese Pinna; Carlo Tascini; Matteo Bassetti; Francesco Giuseppe De Rosa; on behalf of SITA GIOVANI (Young Investigators Group of the Società Italiana Terapia Antinfettiva) (MDPI AG, 2022)
Background: infective endocarditis (IE) remains a severe disease frequently encountered in clinical practice and often requiring interdisciplinary medical and surgical management. This national survey aims to describe the clinical prescribing habits of the use of daptomycin in the setting of IE and the possible role for combination therapy with beta-lactams. Methods: The study was a cross-sectional internet-based questionnaire survey on therapy with daptomycin. The questionnaire was designed with closed-ended questions and distributed using the SurveyMonkey® platform between October 2019 to December 2020. Results: 55 clinicians from twelve Italians regions joined the questionnaire. The survey reported use of daptomycin as first-line choice in 31.48% of cases and as the first-line anti-MRSA agent in 44.44%. The empiric use of daptomycin was stated in the high suspicion of MRSA rather than MSSA, enterococcal or streptococcal IE. The rationale of daptomycin for the empirical treatment of native and prosthetic valve IE was mostly the possibility of administering an aminoglycoside-sparing combination regimen, high bacterial killing rate and high clinical efficacy. Conclusions: In conclusion, in selected patients, daptomycin could be a feasible option for the treatment of infective endocarditis in line with data from the European registry of daptomycin.